(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Lumbosacral spinal canal stenosis is a common cause for chronic low back pain. The diagnosis is mostly radiological, yet, the extent of neural impairment cannot be expressed by radiological means. It is hypothesized that somatosensory evoked potential indicate a nerve root involvement complementary to the neurological examination. Objectives:To evaluate the usefulness of different parameters of mixed somatosensory evoked potential in the diagnosis of lumbosacral stenosis. Methods: Thirty five patients with Lumbosacral stenosis, clinically and radiologically confirmed by MRI examination and 20 normal individuals were enrolled in the study. Mixed-somatosensory evoked potentials of tibial nerve was done using subdermal monopolar needle electrodes at 4 channels; cortical, lower thoracic, lumbar and popliteal. From these channels negative waves (N45, N25, N20 and N10) were studied for both latency and amplitude, besides the central sensory conduction time which represents inter-peak latency between N25 and N45. Results:The cutoff values of N25, N45 and N20 wave latencies presented highly significant differences between affected sides and controls; with the highest difference given by N25 wave (P< 0.0001). There was no significant difference regarding N10 and N25-N45 latencies. The mixed somatosensory wave amplitude cutoff values showed equivocal results about the sensitivity and specificity percentages. Conclusions:Mixed somatosensory evoked potential study can be used as a supplementary test in the diagnosis of Lumbosacral stenosis. N25 wave has the highest diagnostic yield due to having the highest sensitivity and specificity. Equivocal results of the evoked potential amplitudes and their lower sensitivities and specificities compared to evoked potential latencies, lower their validity in the diagnosis of Lumbosacral spinal stenosis. Keyword: Cutoff, sensitivity, specificity, referred.